Rectangular Plate Rebound Vibration Suppression using Double Collision Phenomena - Matsumoto, Hiroki; Kawakita, Kazuhiro (EPI International Journal of Engineering, 2023)
The rectangular plate is a model of the internal mirror of an SLR camera. The internal mirror model is a rectangular metal plate that rotates on its own axis around one side of a rectangle. When the mirror hits to the stopper, a rebound vibration occurs. The double collision method is introduced to reduce the rebound vibration. The timing of the double collision varies the amount of rebound vibration. 3-D Particle Image Velocimetry (3-D PIV) and 3-D motion analysis are used to investigate the rebound phenomena. 3-D PIV measures the rebound vibration velocity of the mirror model surface at the moment of collision. 3-D motion analysis is used to measures the rebound vibration displacement at the moment of collision. When the rebound vibration is small, the low-velocity region on the surface of the mirror model moves in the longitudinal direction. This indicates that the mirror model is undergoing wave deformation after the moment of collision. When the timing of the second collision is optimized, the deformation of the mirror model at the moment of collision is increased and the rebound amount is suppressed.